ChemInform Abstract: Efficient Imidazolium Salts for Palladium‐Catalyzed Mizoroki—Heck and Suzuki—Miyaura Cross‐Coupling Reactions. Issue 46 (24th October 2013) - Amini, Mojtaba; Bagherzadeh, Mojtaba; Rostamnia, Sadegh
Abstract Novel imidazolium salts, precursors of N‐heterocyclic carbenes, are prepared and applied as ligands in the title reactions.